Pengembangan Teknik Pembelajaran Inovatif Mind Mapping in Learning Journal (MMILJ) untuk Peningkatan Self-Regulated Learning (SLR) - Satar, Suriyah; Nurbaya, Nurbaya; Listiani, Hanida (Universitas Nusantara PGRI Kediri, 2025)
This research is a development research that aims to develop a valid learning design with Mind Mapping in Learning Journal technique in the Teaching and Learning Strategy course. The Model of development used is the 4D Model which four stages, there are Define, Design, Develop, and Disseminate. In the Develop stage, the researcher conducted a feasibility test by material experts, language experts and curriculum experts. The development of learning design with the Mind Mapping in Learning Journal technique resulted in several learning devices, namely (1) Design for the implementation of the Mind Mapping in Learning Journal learning technique, (2) Semester Lecture Plan for the Teaching and Learning Strategy course with the Mind Mapping in Learning Journal learning technique and Lecture Reference Unit for 16 meetings with the Mind Mapping in Learning Journal technique. The validation results obtained were the aspect of material suitability in the very valid category, the language aspect in the valid category and the content aspect in the very valid category and the time allocation aspect was very valid. The average validation results were stated to be very valid to be used as a learning device in the Teaching and Learning Strategy course and quite effective to be used in improving Self Regulated Learning of Biology Education students.